Pelatihan Topologi Jaringan Menggunakan Cisco Packet Tracer untuk Meningkatkan Kompetensi Mahasiswa Politeknik Angkatan Darat Malang - Priska Choirina; Muhammat Maariful Huda; Urnika Mudhifatul Jannah; Satria Utama; Erlillah Rizqi Kusuma Pradani (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The positive value of the internet is that the information generated can facilitate everyday human work. One of the negative impacts caused by the internet is cyber crime. As the Indonesian Army who is conducting studies at the Politeknik Angkatan Darat, it is not only required to be professional and proficient in physical warfare strategies. But it also has to be sophisticated and not technologically illiterate in dealing with all threats in cyberspace, including cyber crime. One of the basic sciences for dealing with cyber crime is computer networks by implementing the concept of network topology. Network topology simulation training using packet tracer software in the context of community service activities has the aim of providing technological concepts about the use of packet tracers along with network topology simulations. This training begins with an introduction to network topology which discusses implementation in military life and its strengths and weaknesses. Furthermore, the implementation of this knowledge into a packet tracer and simulating the network topology. From the participants consisting of telkommil, it is hoped that all of them can take part in the training in order to understand how to design a good computer network using packet tracer software.